8 - ‘Boko Haram is Losing, But so is Food Production’: Conflict and Food Insecurity in Nigeria and Cameroon - Kam Kah, Henry (Africa Development, 2017)
This article examines the chronic food insecurity in parts of Nigeria and Cameroon as a result of the Boko Haram insurgency. This insurgency became active in 2009 and has decimated whole communities, destroyed food crops, killed cattle and forced farmers to flee to protective camps. Many now rely on food aid from international organizations. As Nigeria and its neighbours try to contain the insurgents, a bigger problem has been created or further compounded: that of food insecurity, which has ramifications beyond national borders. Markets have been closed and custom duties have dwindled. This article assesses the ongoing situation.